2012
DOI: 10.1002/aenm.201200087
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Mesoporous MoS2 with Expanded Spacing of the (002) Crystal Plane for Ultrafast Lithium Ion Storage

Abstract: Highly ordered mesoporous MoS2 with a high surface area and narrow pore‐size distribution is synthesized by a vacuum assisted impregnation route. The mesoporous MoS2 demonstrates an expanded d002 spacing of 0.66 nm. The mesoporous MoS2 electrode achieves an excellent high rate capacity of 608 mAh g−1 at the discharge current of 10 A g−1 (∼15C), which places MoS2 as a viable next generation high power source for electric vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
370
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(389 citation statements)
references
References 31 publications
14
370
0
Order By: Relevance
“…123 Liu et al have developed a vacuum assisted impregnation route to prepare a highly ordered mesoporous MoS 2 with expanded d-spacing of the (002) plane (0.66 nm), providing sufficient space for ultra-fast lithium ion intercalation. 124 Similarly, the spacing of the (002) crystal plane was significantly expanded in the hierarchical MoS 2 nanoflake array/carbon cloth, thereby the high specific capacity, good cycling stability, and the predominant rate performance were achieved. 125 Supercapacitors are also one of the most widely studied energy storage devices due to their high power density, high rate capability and long cycle life.…”
Section: Applications In Energy Storage Devicesmentioning
confidence: 91%
“…123 Liu et al have developed a vacuum assisted impregnation route to prepare a highly ordered mesoporous MoS 2 with expanded d-spacing of the (002) plane (0.66 nm), providing sufficient space for ultra-fast lithium ion intercalation. 124 Similarly, the spacing of the (002) crystal plane was significantly expanded in the hierarchical MoS 2 nanoflake array/carbon cloth, thereby the high specific capacity, good cycling stability, and the predominant rate performance were achieved. 125 Supercapacitors are also one of the most widely studied energy storage devices due to their high power density, high rate capability and long cycle life.…”
Section: Applications In Energy Storage Devicesmentioning
confidence: 91%
“…The mesoporous MoS 2 nanostructures have a specific surface area as high as 130 m 2 g −1 and the corresponding LIB exhibits an excellent rate capacity of 608 mA h g −1 at a high current of 10 A g −1 and delivers a high discharge capacity of 876 mA h g −1 after 100 cycles at current of 100 mA g −1 . [95] Lou et al reported synthesis of hierarchical MoS 2 hollow nanospheres by a sulfidation reaction of Mo-glycerate solid spheres. The hierarchical hollow nanospheres consisting of interlayerexpanded MoS 2 nanosheets with an interlayer distance of 0.66 nm deliver a high capacity of about 1100 mA h g −1 at 0.5 A g −1 with good rate retention and long cycle life (100 cycles).…”
Section: Application In Lithium Ion Batteries (Libs)mentioning
confidence: 99%
“…1,2 Owing to its structural, electronic and electrochemical features, MoS 2 has been explored as the active material for various devices, including fieldeffect transistors, 3 light-emitting diodes, 4 biosensors, 5 lithium-ion batteries (LIBs) and hydrogen production. [6][7][8][9][10] MoS 2 shows a number of advantageous features when used as the anode of LIBs. First, MoS 2 has a theoretical specific capacity of 670 mAh g − 1 , which is almost double the capacity of graphite, the dominant anode material of current commercial LIBs.…”
Section: Introductionmentioning
confidence: 99%